Dictaduras y gobiernos autoritarios en Iberoamérica en el siglo XX: Violencia, derechos humanos y procesos de construcción de la memoria - Palacios, Julián Chaves (Diálogos Latinoamericanos, 2013)
Latin America launched in the second half of the twentieth century an example of political destabilization due to initiatives such as the National Security Doctrine, which was fostered by U.S. special scope in most countries of the American continent. The product of political destabilization and coups implementing dictatorial and authoritarian political systems was the norm. Military regimes, in many cases, prolonged their existence for decades and were in the systematic violation of human rights the basis of their livelihood. Executions, disappearances, arrests and exile formed their code of conduct as most effective way to control dissent. Protests against these outrages by the affected families and representative associations succeeded in promoting democratic governments, public policies to clarify what happened and give dignity and justice to the repressed.